Development of the Unified Security Requirements of PUFs During the Standardization Process - Bruneau, Nicolas; Danger, Jean-Luc; Facon, Adrien; Guilley, Sylvain; Hamaguchi, Soshi; Hori, Yohei; Kang, Yousung; Schaub, Alexander (Innovative Security Solutions for Information Technology and Communications, 2019)
This paper accounts for some scientific aspects related to the international standardization process about physically unclonable functions (PUFs), through the drafting of ISO/IEC 20897 project. The primary motivation for this standard project is to structure and expand the market of PUFs, as solutions for non-tamperable electronic chips identifiers. While drafting the documents and discussing with international experts, the topic of PUF also gained much maturity. This article accounts how scientific structuration of the PUF as a field of embedded systems security has been emerging as a byproduct. First, the standardization has allowed to merge two redundant security requirements (namely diffuseness and unpredictability) into one (namely randomness), which in addition better suits all kinds of PUFs. As another contribution, the standardization process made it possible to match unambiguous and consistent tests with the security requirements. Furthermore, the process revealed that tests can be seen as estimators from their theoretic expressions, the so-called stochastic models.